MicroRNA-206 inhibition and activation of the AMPK/Nampt signalling pathway enhance sevoflurane post-conditioning-induced amelioration of myocardial ischaemia/reperfusion injury. (2nd January 2020) - Li, Tao; Yu, Shan-Shan; Zhou, Chang-Yu; Wang, Ke; Wan, Ying-Chun
Abstract: This study aimed to investigate the effect of miR-206 on apoptosis and autophagy of cardiomyocytes in ischaemia/reperfusion (I/R) injured rats treated with sevoflurane post-conditioning (SP) through the AMPK/Nampt signalling pathway. Rat models of myocardial I/R injury were established. The combination of SP, miR-206 inhibitor, AMPK activator AICAR and inhibitor Compound C was induced in rats, and their effects on I/R injury were determined with detection of malondialdehyde (MDA), hydroxyproline (HYP) and superoxide dismutase (SOD) levels in cardiomyocytes, autophagy, and apoptosis. We also conducted experiments to determine p62, Beclin1, Bax and Bcl-2 expression and the mRNA and expression pattern of AMPK/Nampt signalling pathway-related genes. Myocardial I/R injured rats revealed decreased SOD activity and elevated MDA content, autophagy and apoptosis. With the combined performance of SP, miR-206 inhibitor and AMPK activator AICAR, the rats presented higher SOD level and lower MDA and HYP levels, suppressed autophagy and apoptosis. Meanwhile, miR-206 inhibition also contributed to elevated expression of Nampt and the extent of AMPK phosphorylation, increased Bcl-2/Bax ratio, but degraded expression of p62 and Beclin1. Collectively, inhibition of miR-206 could activate the AMPK/Nampt signalling pathway, thus protecting against myocardial I/R injury on the basis of SP.